A potential material for hydrogen storage: a Li decorated graphitic-CN monolayer. Issue 19 (4th May 2018) - Chen, Yong-Dao; Yu, Song; Zhao, Wen-Hui; Li, Shun-Fang; Duan, Xiang-Mei
Abstract : Motivated by recent experimental developments of graphitic-CN (g-CN) sheets, we investigate the suitability of hydrogen storage on Li decorated g-CN via first-principles calculations. Abstract : Motivated by recent experimental developments of graphitic-CN (g-CN) sheets, we investigate the suitability of hydrogen storage on Li decorated g-CN via first-principles calculations. We find that the binding energies of Li atoms are very large, ranging from 2.70 to 4.73 eV, which are significantly higher than the cohesive energy of bulk Li. Lithium atoms therefore tend to form 2D rather than 3D patterns on g-CN, promoting reversible hydrogen adsorption and desorption. Remarkably, the average adsorption energy of H2 molecules falls in the 0.14–0.23 eV range, and the Li decorated CN shows a high theoretical gravimetric density of 10.81 wt%, which is favorable for massive hydrogen storage. Our results suggest that the Li decorated CN could be a promising hydrogen storage material under realistic conditions.